KEABSAHAN TRANSAKSI DAN RISIKO PRODUK CACAT DI SHOPEE: ANALISIS NORMATIF Undang-Undang Nomor 8 Tahun 1999 - Zaki Kaisar Syah; Muhlizar Muhlizar; Zuhri Arif (UIN Sumatera Utara, 2025)
Abstact: This article examines the legal validity of online transactions and the allocation of risks related to defective products on the Shopee marketplace from a normative juridical perspective. Using the framework of Law No. 8 of 1999 concerning Consumer Protection, the study analyzes the extent to which electronic transactions meet legal requirements and how consumer rights are guaranteed when goods received are damaged or do not conform to the order. The research highlights the responsibilities of business actors, the legal position of consumers, and the mechanisms available for dispute resolution within the platform. The findings show that although Shopee provides internal complaint and refund features, the substantive protection of consumers still relies heavily on the provisions of national consumer law, particularly regarding liability, misleading information, and the obligation to provide goods in accordance with agreed specifications. This article concludes that strengthening legal certainty and enforcement mechanisms is essential to ensure fair and accountable e-commerce practices in Indonesia.Keywords: Legal regulations, Consumer Protection, Sales and Purchase Agreement, Shopee, Defective Products.